Navigating Challenges and Opportunities: Homestay Business Dynamics in Indonesia's Tourism Landscape - Muhamad Iqbal Tawakal (Co-Value Jurnal Ekonomi Koperasi dan kewirausahaan, 2024)
This study investigates the role of homestay entrepreneurship in promoting sustainable tourism in Indonesia, emphasizing its impact on community involvement and local economic growth. By contextualizing homestays within the broader tourism framework, the research highlights their significance in providing authentic cultural experiences that cater to modern travellers' preferences for deeper connections with destinations. Key findings reveal that community involvement enhances guest experiences and fosters a sense of ownership among residents, aligning with existing literature advocating for community-based tourism. Additionally, integrating technology and effective marketing strategies is crucial for increasing visibility and engagement among homestay operators, showcasing the importance of adapting to digital trends in a competitive landscape. The study also addresses homestay entrepreneurs' challenges, particularly in light of global disruptions such as the COVID-19 pandemic, while highlighting their resilience and adaptability in navigating these obstacles. Overall, the research underscores the potential of homestay entrepreneurship to drive sustainable tourism while empowering local communities. Future research is encouraged to explore the long-term impacts of these dynamics on local communities and the tourism ecosystem, ensuring equitable and sustainable tourism development in the region.